Impact Assessment of Sorption Properties of Coal on Methane Emissions Into Longwall Working - Koptoń, Henryk (Archives of Mining Sciences, 2020)
A mathematical model for the purposes of methane hazard assessment in mines was developed in the Central Mining Institute as part of the statutory activities conducted in 2017 and 2018. The model describes the course of kinetics of methane sorption on coal samples while taking into account the diffusion coefficient. The paper presents the formulas describing the mathematical model of methane emission from coal sidewall to longwall working, taking into account the sorption properties of coal – sorption capacity of coal (related to methane) and the effective diffusion coefficient of methane in coal. In the light of the conducted research, such a methodology for describing this phenomenon enables a more precise determination of the amount of methane released to the longwall from the exploited coal seam, which in turn makes it possible to select appropriate methane prevention measures.
Keywords: mining; methane; physical chemistry; sorption